Psychological Features of Post-Traumatic Stress Disorder in the Civilian Population of a Region Exposed to Local Military Actions (Using the Example of Mariupol) - A.M. Bogachev; Yu.A. Vysotskaya; T.G. Vintonyuk (Клиническая и специальная психология)
The work aims to study the relationship between the level of risk of PTSD, coping strategies, psychological defense mechanisms and other manifestations of personality traits. Materials from an empirical study conducted on a sample of students at the Mariupol State University named after A.M. Kuindzhi are presented. Sample. The study involved 99 respondents aged 18–35 years, with data from a female subgroup of 90 individuals, averaging 21.09 years old. Methods used included the Trauma Screening Questionnaire for screening post-traumatic stress disorder, the Ways of Coping Questionnaire (WCQ) adapted in Russian by L.I. Wasserman and the Self-Report of Defense Styles questionnaire by M. Bond, adapted in Russian by E.E. Tunik. Additionally, the Scale of Reactive and Personal Anxiety by C.D Spielberger was used in its Russian-language adaptation by Y.L. Hanin, Hospital Anxiety and Depression Scale (HADS), Pittsburgh Questionnaire for Determining the Sleep Quality Index (Pittsburgh Sleep Quality Index, PSQI), Spiegel Scale of Subjective Sleep Characteristics (Medical Outcomes Study Sleep Scale, MOS-SS), Epworth Sleepiness Scale author’s questionnaire. Results. The results obtained allow us to say that a high risk of PTSD development is related to the coping strategy “escape–avoidance”, maladaptive personality defenses, and subjective sleep disorders, such as nightmares and insomnia.